2016
DOI: 10.1016/j.jpainsymman.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The Trajectory of Dyspnea in Hospitalized Patients

Abstract: Context The trajectory of dyspnea for patients hospitalized with acute cardiopulmonary disease, who are not terminally ill, is poorly characterized. Objectives To investigate the natural history of dyspnea during hospitalization, and examine the role that admission diagnosis, and patient factors play in altering symptom resolution. Methods Prospective cohort study of patients hospitalized for an acute cardiopulmonary condition at a large tertiary care center. Dyspnea levels and change in dyspnea score were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…We found that discrepancy between patients and healthcare providers was more pronounced for patients with COPD. In another study using the same patient cohort, we reported that compared to patients with congestive heart failure, those with COPD had more residual dyspnea at discharge; 1 in 4 patients was discharged with a dyspnea score of 5 of greater, and almost half reported symptoms above their baseline . The results from the current study may explain in part why patients with COPD are discharged with higher levels of dyspnea and should alert healthcare providers on the importance of patient‐reported breathlessness.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We found that discrepancy between patients and healthcare providers was more pronounced for patients with COPD. In another study using the same patient cohort, we reported that compared to patients with congestive heart failure, those with COPD had more residual dyspnea at discharge; 1 in 4 patients was discharged with a dyspnea score of 5 of greater, and almost half reported symptoms above their baseline . The results from the current study may explain in part why patients with COPD are discharged with higher levels of dyspnea and should alert healthcare providers on the importance of patient‐reported breathlessness.…”
Section: Discussionmentioning
confidence: 53%
“…In another study using the same patient cohort, we found that compared tp patients with CHF, those with COPD had more residual dyspnea at discharge; one in four patients was discharged with a dyspnea score of 5 of greater, and almost half reported symptoms above their baseline. (24) The results from the current study may explain in part why patients with COPD are discharged with higher levels of dyspnea and should alert healthcare providers on the importance of patient reported breathlessness. Third, the high level of discordance between healthcare providers and patients may explain the under-treatment of dyspnea in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 82%
“…During hospitalization for an acute exacerbation (AECOPD), functional exercise capacity and quadriceps muscle strength are negatively impacted [ 7 , 8 , 9 ]. Assessment of physical functioning at the end of an AECOPD-related hospitalization may be difficult in patients with COPD, as they may still suffer from severe dyspnea and fatigue [ 10 , 11 ]. However, this may provide an important indication for early referral for pulmonary rehabilitation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, chest pain, another common ED complaint, is associated with a much lower rate of readmission 24 . Altogether, our results suggest that readmission may be linked to the persistent underlying disease despite seemingly resolved symptoms 25 . There is an urgent need of randomized trials investigating if diagnostic work‐up and short and long‐term personalized management of patients with acute dyspnoea including biomarkers and/or lung ultrasound could improve prognosis of this heterogeneous patient group.…”
Section: Discussionmentioning
confidence: 77%
“…24 Altogether, our results suggest that readmission may be linked to the persistent underlying disease despite seemingly resolved symptoms. 25 There is an urgent need of randomized trials investigating if diagnostic work-up and short and long-term personalized management of patients with acute dyspnoea including biomarkers and/ or lung ultrasound could improve prognosis of this heterogeneous patient group. Our data also urge, in case of heart failure, the rapid implementation of guideline-recommended therapies.…”
Section: Discussionmentioning
confidence: 99%